Evaluation of hand hygiene practices among patients visiting dental college of purvanchal region - A cross-sectional study - Mahesh Ravindra Khairnar; Vinay Kumar Srivastava; Ananta Kusumakar; Adit Srivastava; Rahul Agrawal; Akhilesh Chandra; P G Naveen Kumar; Zainab Akram (Wolters Kluwer Medknow Publications, 2022)
Background: Effective hand hygiene is one of the most cost-efficient means of preventing infectious diseases in the community. Studies conducted to assess the hand hygiene practices of the general population in India are relatively limited. The present study was conducted with the aim to assess hand hygiene practices among the participants visiting the outpatient department (OPD) of a dental institute in the Purvanchal region in India. Materials and Methods: This cross-sectional study was conducted on 880 participants visiting the OPD of a dental college in the Purvanchal region. The data were collected using a pretested questionnaire focusing on the hand hygiene practices of the participants. Statistical analysis was done using Chi-square test and the level of significance was set at 5%. Results: Results showed that 98.5% of the respondents used soap/antiseptic liquid soap or hand sanitizer. The frequency of handwashing increased with the improvement in socioeconomic status, with almost 70% of upper-class participants washing their hands daily 5-6 times or more (P = 0.001). A significant association was seen between education and extension of handwashing (P = 0.001). Conclusion: Majority of the population were using soap and water for handwashing which shows that people are aware that proper hand hygiene is necessary to prevent the spread of infectious diseases, especially COVID-19. However, more work is needed to educate people from lower socioeconomic status about good hand hygiene practices.